Cittadinanza e disabilità: Giurisprudenza e Dottrina a confronto - Sforza, Irene (Cultura giuridica e diritto vivente, 2014)
[Citizenship and Disability: A Comparison between Court Decisions and Doctrine]. The article proposes to tackle the difficult combination between most personal acts and the necessary representation in the field of citizenship. In particular, it focuses on the legal opportunity of allowing a declaration of intention aimed at the purchase of the status civitatis to be made by the lawyer of a foreigner. This may occur in two precise moments: at the presentation of the request of admission and at the submission of the oath of allegiance ex art. 10 L. 91/1992. The author's overall support is based on some judicial tendencies and on the major jurisprudential theories concerning capacity/competence.